Nursing students in isolation during the COVID-19 pandemic: A phenomenological study - Vistolina Nuuyoma; Frieda Makambuli (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences)
Background: Isolation as a public health practice encompasses physical and social separation of individuals from others, and it was key in preventing human-to-human spread of the coronavirus disease 2019 (COVID-19) virus. Yet, experiences of patients in isolation have been mostly studied in the general population and qualified health professionals, excluding nursing students who were also part of the frontliners and therefore, part of the population at risk of infections.